2008
DOI: 10.1038/nn2040
|View full text |Cite
|
Sign up to set email alerts
|

Action potential generation requires a high sodium channel density in the axon initial segment

Abstract: The axon initial segment (AIS) is a specialized region in neurons where action potentials are initiated. It is commonly assumed that this process requires a high density of voltage-gated sodium (Na(+)) channels. Paradoxically, the results of patch-clamp studies suggest that the Na(+) channel density at the AIS is similar to that at the soma and proximal dendrites. Here we provide data obtained by antibody staining, whole-cell voltage-clamp and Na(+) imaging, together with modeling, which indicate that the Na(+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

54
613
4
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 606 publications
(689 citation statements)
references
References 50 publications
54
613
4
3
Order By: Relevance
“…Indeed, recordings from patches excised from axonal blebs reveal a much higher current density than those obtained from the soma [1] , consistent with immunostaining results and the finding of significantly larger peak Na + currents in cell-attached patches from intact AIS than those at the soma after depolymerizing actin filaments [19] . Recordings from blebs formed at the AIS also revealed that axonal Neurosci Bull August 1, 2012, 28(4): 342-350 346 action potentials have higher peak amplitudes and faster rising phases than somatic ones [33] , indicating a high density of axonal Na + channels.…”
Section: Axonal Bleb Recordingsupporting
confidence: 85%
See 4 more Smart Citations
“…Indeed, recordings from patches excised from axonal blebs reveal a much higher current density than those obtained from the soma [1] , consistent with immunostaining results and the finding of significantly larger peak Na + currents in cell-attached patches from intact AIS than those at the soma after depolymerizing actin filaments [19] . Recordings from blebs formed at the AIS also revealed that axonal Neurosci Bull August 1, 2012, 28(4): 342-350 346 action potentials have higher peak amplitudes and faster rising phases than somatic ones [33] , indicating a high density of axonal Na + channels.…”
Section: Axonal Bleb Recordingsupporting
confidence: 85%
“…For example, the AIS of layer-5 pyramidal cells has a larger diameter (1-2.5 μm) than the rest of the axonal compartment (0.1-1 μm) and thus is accessible to patch pipettes [18][19][20][21] .…”
Section: Establishment Of the Tight-seal Patch-clamp Techniquementioning
confidence: 99%
See 3 more Smart Citations